Gastrointestinal Stromal Tumor (GIST) and its relationship with germline mutations - Arranz-Salas, Isabel María; Jiménez-Campillo, Marta; Hierro-Martín, María Isabel; Ortega-Jiménez, María Victoria; Mercado-Sáenz, Silvia; Rodríguez-Pérez, Luis Manuel; Sánchez-Varo, Raquel María; Escamilla-Sánchez, Alejandro; Peláez-González, Alberto Carlos; Bermúdez-Flores, Diego Teófilo (My University, 2022)
We present the case of a 38-year-old man with a history of abdominal paraganglioma 10 years ago, who consulted for hematemesis and asthenia of 5 days' evolution. An upper gastrointestinal endoscopy was performed where a raised submucosal lesion, about 2 cm, with ulceration on its surface, was observed at the corporal-antral junction. The CT scan revealed nodular thickening of the gastric wall at the level of the lesser curvature. After the resolution of his hematemesis, it was decided to intervene on the patient, performing a partial gastrectomy
Keywords: Cáncer - Histopatología; GIST; Gastric cancer; Molecular